2016
DOI: 10.1111/jgh.13181
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide insufflation during colonoscopy can significantly decrease post‐interventional abdominal discomfort in deeply sedated patients: A prospective, randomized, double‐blinded, controlled trial

Abstract: Compared with air, CO2 insufflation during colonoscopy reduced postcolonoscopy abdominal discomfort and improved patients' satisfaction. It was safe to use CO2 insufflation in deeply sedated colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Forty RCT with 13 734 patients were included from 1060 articles searched through databases and other sources (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty RCT with 13 734 patients were included from 1060 articles searched through databases and other sources (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐three studies focused on the analysis regarding cecal intubation time. According to our analysis, we did not get any significant results on cecal intubation time.…”
Section: Resultsmentioning
confidence: 99%
“…CO 2 is absorbed from the bowel more rapidly than air, resulting in a reduction in post‐endoscopic gas volume. Many studies have shown that CO 2 insufflation reduces abdominal pain and distention during and post colonoscopy . Several studies have also demonstrated that CO 2 insufflation is safe and has no significant adverse events .…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study with moderate sedation found that there was no difference in patient discomfort and satisfaction regarding the procedure sequence . Because carbon dioxide (CO 2 ) is absorbed across the intestines more rapidly than air, CO 2 insufflation has commonly been used in colonoscopies to decrease abdominal discomfort during and e after the procedure . The gas insufflation during EGD‐related difficult colonoscopy intubation might be minimized by applying CO 2 insufflation.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have objectively evaluated the level of residual bowel gas following this procedure. Chen et al (39), observed that CO 2 insufflation significantly reduced the volume of residual bowel gas compared with air insufflation following colonoscopy by using abdominal radiography. To the best of our knowledge, the present study is the first to objectively evaluate the degree of bowel distention following colorectal ESD using CT examination.…”
Section: Discussionmentioning
confidence: 99%